Influência da disponibilidade de alimento sobre o tamanho corpóreo e abundância de rotíferos e cladóceros em áreas alagáveis subtropicais. - Bomfim, Francieli de Fátima (2016)
Aquatic communities are influenced by food availability, changing its structuring, reflecting the interactions between organisms and, therefore, the bioenergetics relationships in the food chain. We had to analyze the change of phytoplankton biomass and abundance of ciliated protozoa alters the body size distribution of rotifers and cladocerans and their abundances in the different size classes structuring these communities. The hypothesis that environments where there is greater availability of food will be more abundant and predominance of smaller organizations; the opposite is expected for environments with lower availability of resources, which will lower abundance and dominance of larger organisms. Significant positive relationships were observed between the classes of small size of rotifers and small and mid-size class cladocerans and the concentration of chlorophyll-a and abundance of ciliates. Lower classes size of both groups dominated environments with higher resource availability, while the classes of greater Cladocera size dominated environments with lower resource availability, suggesting competitive advantage of large cladocerans on other rotifers and cladocerans when is scarce.